Modification method of nano zinc oxide and colored asphalt
By performing low-temperature plasma surface treatment and polyacrylamide treatment on nano zinc oxide, the number of surface functional groups is increased, and the problem of poor performance of colored asphalt in high and low temperature environments is solved, and the effect of improving its antioxidant performance and elastic properties is achieved. , while avoiding the problem of increasing viscosity.
Patent Information
- Application Number
- CN202311018993.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-14
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-08-14
AI Technical Summary
The existing colored asphalt has poor performance in high and low temperature environments, poor oxidation resistance, and the viscosity increases after modification of nanomaterials, which limits its application.
By subjecting the nano zinc oxide to a low-temperature plasma surface treatment, the number of surface functional groups is increased, and mixed with the aqueous polyacrylamide solution for stirring and drying, modified nano zinc oxide is obtained and added to colored asphalt to improve its performance.
It improves the high-temperature, anti-aging and elastic properties of colored asphalt, avoids the increase in viscosity, and enhances its low-temperature self-healing and anti-oxidation ability.
Abstract
Description
Technical Field
[0001] The invention discloses a modification method of nano zinc oxide and colored asphalt, belonging to the technical field of asphalt modifiers. Background Art
[0002] Colored asphalt is a binder with the properties of petroleum asphalt prepared from base oil, petroleum resin and modifier as raw materials. Due to the large amount of low-viscosity base oil added in the colored asphalt, the high-temperature performance of the colored asphalt is poor, and the petroleum resin is a copolymer of C5~C9 components, which contains a certain amount of unsaturated bonds inside, and is easily oxidized at high temperatures to form free radicals, thereby reducing the antioxidant properties of the modified colored asphalt. In addition, the petroleum resin is a brittle solid at room temperature and has low elasticity, which makes the modified colored asphalt have poor elastic properties at low temperatures, resulting in poor self-healing properties. The base oil also contains some unsaturated components, which will also undergo oxidation reactions, resulting in poor anti-aging performance of the colored asphalt. The modifiers used in the preparation process of colored asphalt in the prior art are all polymers, and the unsaturated components inside them will undergo partial thermal degradation as the temperature rises, resulting in a decrease in the high-temperature performance of the colored asphalt.
[0003] Since the surface of nano zinc oxide has a certain amount of surface active groups, adding it to modified asphalt can improve the high temperature performance and anti-aging performance of asphalt. This is because nanomaterials are inorganic materials and cannot be completely dissolved in asphalt. They can only use the functional groups on the surface to undergo physical and chemical reactions with the components in the asphalt to form a complex, thereby improving the performance of asphalt. Therefore, the degree of modification effect of nanomaterials is closely related to the number of functional groups on its surface. The more functional groups there are, the better the modification effect. However, as the number of surface functional groups of nanomaterials increases, their surface energy increases, resulting in poor dispersibility, causing nanomaterials to agglomerate in modified asphalt, and the viscosity of modified asphalt increases significantly, resulting in poor modification effect, which limits the application of nanomaterials in modified asphalt.
[0004] Patent CN116376304A discloses a modified asphalt and its preparation method and application. The asphalt modifier used therein increases the low-temperature ductility, low-temperature crack resistance and aging resistance of the asphalt. However, the zinc oxide used in the asphalt modifier is only used as a stabilizer, mainly utilizing the modification effect of rubber, and the nano-calcium carbonate used therein will also increase the viscosity of the asphalt, failing to solve the problem of increased viscosity caused by nano-material modification. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a method for modifying nano zinc oxide and colored asphalt which can improve the antioxidant capacity and high and low temperature performance of asphalt without increasing the viscosity of asphalt.
[0006] The technical solution adopted by the present invention to solve the technical problem is: a modification method of nano zinc oxide, characterized in that it comprises the following steps: 1) Nano zinc oxide is surface treated by low temperature plasma; 2) Add nano zinc oxide to a polyacrylamide aqueous solution with a weight concentration of 0.5-1% at a rotation speed of 4000-6000 rpm and stir for 30-60 minutes; 3) Separate, wash and dry to obtain modified nano zinc oxide.
[0007] By increasing the number of functional groups on the surface of nano-zinc oxide and solving the problem of difficulty in dispersing nano-zinc oxide caused by the increase in the number of functional groups, the increase in asphalt viscosity after adding asphalt can be avoided. This can not only improve the high temperature performance and anti-aging properties of colored asphalt, but also improve the elastic properties of modified colored asphalt and improve its low-temperature self-healing properties.
[0008] Preferably, the conditions for the low-temperature plasma surface treatment in step 1) are: a volume ratio of nitrogen to oxygen of 1.5 to 9:1, a gas flow rate of 15 to 30 L / min, a voltage of 20 to 30 kV, and a frequency of 6 to 10 kHz.
[0009] Preferably, the low-temperature plasma surface treatment in step 1) lasts for 1 to 5 minutes.
[0010] Preferably, the nano zinc oxide in step 1) is first soaked in deionized water for 60 to 100 minutes before the low-temperature plasma surface treatment.
[0011] Preferably, the preparation method of the polyacrylamide aqueous solution in step 2) is: after mixing water and polyacrylamide, the mixture is grown at a constant temperature of 50-70° C. for 20-40 minutes to obtain the polyacrylamide aqueous solution.
[0012] A colored asphalt, characterized in that the raw materials include 57-68 parts of petroleum resin, 24-32 parts of base oil, 5-10 parts of SBS polymer and 1-4 parts of the above-mentioned nano zinc oxide in parts by weight.
[0013] Preferably, the petroleum resin is one or more of coumarone resin, terpene resin and semi-hydrogenated petroleum resin.
[0014] Preferably, the base oil is one or both of cycloparaffinic oil and high aromatic oil.
[0015] Preferably, the preparation method comprises the following steps: 1) After the base oil and SBS polymer are mixed, they are grown at a constant temperature of 130-140°C for 40-60 minutes, heated to 150-160°C, and nano zinc oxide is added at a stirring speed of 1000-2000 rpm, and stirring is continued for 30-50 minutes: 2) Add petroleum resin, continue stirring for 30-40 minutes after the petroleum resin is dissolved, and then place it in a constant temperature environment of 140-150℃ for 60-100 minutes.
[0016] Mix the SBS polymer with the base oil in advance, and the SBS polymer absorbs the light components in the base oil and swells, and the intertwined polymer chains are opened, which is conducive to the rapid formation of a three-dimensional network structure of the SBS polymer, and can better exert the modification effect. Mix the modified nano zinc oxide with the base oil in advance, and the thickener wrapped by the modified nano zinc oxide can be dissolved in the low-viscosity base oil, which is conducive to the performance of the modified nano zinc oxide. The addition of petroleum resin can appropriately increase the viscosity of the colored asphalt to a certain extent (different from the sudden increase in viscosity caused by nano materials), and improve the high-temperature performance of the colored asphalt.
[0017] Compared with the prior art, the present invention has the following beneficial effects: the surface of the nano zinc oxide is activated after the plasma discharge treatment, and a large number of activation reaction points are generated. At the same time, the hydrogen supply agent and the oxygen supply agent react at the activation points under the plasma treatment to generate highly reactive hydroxyl groups, thereby increasing the number of hydroxyl active groups on the surface of the nano zinc oxide. The increase in the number of active groups on the surface of the nano zinc oxide makes the nano zinc oxide have a higher reactivity. In the high temperature and air atmosphere, the nano zinc oxide can preferentially replace the unsaturated bonds in the base oil and petroleum resin to combine with oxygen and undergo an oxidation reaction, thereby avoiding the oxidation of components in the colored asphalt and improving the anti-aging performance of the colored asphalt. At the same time, the increase in the number of active functional groups on the surface of the nano zinc oxide can be inserted into the molecular chain of the polymer modifier and undergo a physical and chemical reaction with the polymer molecular chain, thereby forming a compact structure inside the polymer molecule, thereby preventing the polymer from being thermally decomposed at high temperatures, thereby improving the anti-aging performance of the colored asphalt. In addition, the increase in the number of active functional groups on the surface of nano zinc oxide not only increases the contact area between nano zinc oxide and asphalt, but also forms a molecular binding force between nano zinc oxide and asphalt and polymer modifier molecular chains, so that the three form a dense structure. Under the action of external force, nano zinc oxide can absorb more external force, play a reinforcing role, and improve the low-temperature ductility of colored asphalt. At the same time, the increase in the number of active groups on the surface of nano zinc oxide enhances the self-aggregation between nano zinc oxide particles, improves the elastic properties of colored asphalt, and has self-healing properties. In the preparation process of modified asphalt, nano zinc oxide wrapped with thickener can prevent agglomeration caused by a large number of active groups on the surface when added to the modified asphalt, resulting in a poor modification effect. At the same time, the thickener can be dissolved in the modified asphalt, releasing the surface-modified nano zinc oxide, making the nano zinc oxide evenly dispersed, and improving the modification effect of nano zinc oxide. DETAILED DESCRIPTION
[0018] The present invention will be further described below in conjunction with the embodiments, and Embodiment 2 is the best embodiment of the present invention.
[0019] Example 1 A method for modifying nano zinc oxide comprises the following steps: 1) Nano zinc oxide was soaked in deionized water for 70 minutes, filtered and then surface treated in a low-temperature plasma reactor; the conditions for low-temperature plasma treatment were: nitrogen and oxygen volume ratio 5:1, gas flow rate 20L / min, voltage 25kV, frequency 7kHz, and treatment for 5 minutes.
[0020] 2) Water and polyacrylamide were mixed to prepare a polyacrylamide solution with a weight concentration of 1%, and the polyacrylamide solution was obtained by constant temperature development at 60°C for 30 minutes.
[0021] 3) Slowly add nano zinc oxide powder into the polyacrylamide solution at a rotation speed of 4000-6000 rpm and stir for 50 minutes.
[0022] 4) Centrifugal separation, rinsing with deionized water, and drying in an oven at 80°C for 80 minutes to obtain modified nano zinc oxide.
[0023] A colored asphalt, the raw materials of which include: 67kg of petroleum resin, 28kg of base oil, 4kg of SBS polymer and 1kg of modified nano zinc oxide.
[0024] Its preparation method is: 1) After the base oil and SBS polymer are mixed, place them in a 135°C oven for constant temperature development for 50 minutes, heat to 155°C, add modified nano zinc oxide at a stirring speed of 1500 rpm, and continue stirring for 40 minutes.
[0025] 2) Add petroleum resin. After the petroleum resin is dissolved, continue stirring for 35 minutes and place it in a 145°C oven for constant temperature development for 80 minutes to obtain modified colored asphalt.
[0026] Example 2 A colored asphalt, based on Example 1, the raw materials are set as 68kg of petroleum resin, 24kg of base oil, 6kg of SBS polymer and 2kg of modified nano zinc oxide. Other conditions are the same as those in Example 1.
[0027] Example 3 A colored asphalt, based on Example 1, the raw materials are set as 57kg of petroleum resin, 30kg of base oil, 10kg of SBS polymer and 3kg of modified nano zinc oxide. Other conditions are the same as those in Example 1.
[0028] Example 4 A colored asphalt, based on Example 1, the raw materials are set as 64kg of petroleum resin, 26kg of base oil, 8kg of SBS polymer and 2kg of modified nano zinc oxide. Other conditions are the same as those in Example 1.
[0029] Example 5 A colored asphalt, based on Example 1, the raw materials are set as 59 kg of petroleum resin, 31 kg of base oil, 6 kg of SBS polymer and 4 kg of modified nano zinc oxide. Other conditions are the same as in Example 1.
[0030] Example 6 A colored asphalt, based on Example 1, the raw materials are set as 63kg of petroleum resin, 32kg of base oil, 5kg of SBS polymer and 1kg of modified nano zinc oxide. Other conditions are the same as those in Example 1.
[0031] Example 7 A method for modifying nano zinc oxide, based on Example 1, step 1) the volume ratio of nitrogen to oxygen is set to 1.5:1, the gas flow rate is set to 30 L / min, the voltage is set to 30 kV, the frequency is set to 10 kHz, and the time is set to 1 min. Other conditions are the same as in Example 1.
[0032] Example 8 A method for modifying nano zinc oxide, based on Example 1, wherein step 1) the nano zinc oxide is immersed in deionized water for 100 minutes; step 2) the concentration of the polyacrylamide aqueous solution is set to 0.5%, and the constant temperature development time is set to 50° C. for 20 minutes. Other conditions are the same as in Example 1.
[0033] Comparative Example 1 A colored asphalt, based on Example 1, the modified nano zinc oxide in the raw material is replaced by ordinary nano zinc oxide without any surface treatment. Other conditions and the method for preparing the colored asphalt are the same as those in Example 1.
[0034] Comparative Example 2 A method for modifying nano zinc oxide is provided. Based on Example 1, only step 1) is performed, and steps 2) to 4) are not performed. Other conditions and the method for preparing colored asphalt are the same as those in Example 1.
[0035] Comparative Example 3 A method for modifying nano zinc oxide is provided. Based on Example 1, only steps 2) to 4) are performed, and step 1) is not performed. Other conditions and the method for preparing colored asphalt are the same as those in Example 1.
[0036] Comparative Example 4 A colored asphalt, based on Example 1, the preparation method is set as follows: petroleum resin, SBS polymer and modified nano zinc oxide are added to the base oil in sequence, then heated to 150°C, constant temperature development for 50 minutes, stirred at a stirring speed of 1500 rpm for 40 minutes, constant temperature development for 80 minutes to obtain the colored asphalt. Other conditions are the same as in Example 1.
[0037] Comparative Example 5 A colored asphalt, based on Example 1, without adding modified nano zinc oxide, and other conditions are the same as Example 1.
[0038] Performance Testing The performance tests were conducted on the colored asphalt obtained in the above examples and comparative examples. The needle penetration was measured according to the GB / T 4509-2010 method. The softening point was measured according to the GB / T 4507-2010 method. The aging was measured according to the SH / T 0736-2003 method. The 135°C rotational viscosity was measured according to the T0625-2011 method. The elastic recovery test method was NB / SH / T 0816-2010.
[0039] The test results are shown in Table 1 below.
[0040] Table 1 Performance test results .
[0041] According to the performance test results of the above embodiments and comparative examples, by increasing the number of functional groups on the surface of nanomaterials and solving the problem of difficulty in dispersing nanomaterials due to the increase in the number of functional groups, the high temperature performance and anti-aging performance of colored asphalt can be improved, and the elastic performance of modified colored asphalt can be improved, and its low temperature self-healing property can be improved. By modifying nano zinc oxide, it can be found that the addition of modified nano zinc oxide particles significantly improves the softening point and 5°C low temperature ductility of colored asphalt, indicating that the addition of modified nano zinc oxide can significantly improve the high and low temperature performance of colored asphalt; the increase of surface active groups of modified nano zinc oxide can significantly improve the 5°C elastic recovery of modified colored asphalt, so that the modified colored asphalt has good self-healing ability; with the help of the residual ductility after aging, it can be found that the nano zinc oxide after modification can greatly improve the anti-aging performance of modified colored asphalt, and further avoid the significant increase in the viscosity of modified colored asphalt caused by the addition of nano materials. It is further found that the above-mentioned modification method and the color asphalt preparation method have a mutually synergistic and interrelated effect, and jointly improve the performance of colored asphalt.
[0042] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A method for modifying nano zinc oxide, characterized in that: The following steps are involved: 1) Nano zinc oxide is surface treated by low temperature plasma; 2) Add nano zinc oxide to a polyacrylamide aqueous solution with a weight concentration of 0.5-1% at a rotation speed of 4000-6000 rpm and stir for 30-60 minutes; 3) Separate, wash and dry to obtain modified nano zinc oxide.
2. The method for modifying nano zinc oxide according to claim 1, characterized in that: The conditions of the low-temperature plasma surface treatment in step 1) are: nitrogen to oxygen volume ratio of 1.5-9:1, gas flow rate of 15-30 L / min, voltage of 20-30 kV, and frequency of 6-10 kHz.
3. The modification method of nano zinc oxide according to claim 1, characterized in that: The low temperature plasma surface treatment in step 1) is performed for 1 to 5 minutes.
4. The method for modifying nano zinc oxide according to claim 1, characterized in that: The nano zinc oxide in step 1) is first soaked in deionized water for 60 to 100 minutes before the low-temperature plasma surface treatment.
5. The method for modifying nano zinc oxide according to claim 1, characterized in that: The preparation method of the polyacrylamide aqueous solution in step 2) is as follows: after mixing water and polyacrylamide, the mixture is grown at a constant temperature of 50-70° C. for 20-40 minutes to obtain the polyacrylamide aqueous solution.
6. A colored asphalt, characterized in that: The raw materials include 57-68 parts of petroleum resin, 24-32 parts of base oil, 5-10 parts of SBS polymer and 1-4 parts of the nano zinc oxide described in any one of claims 1-5 by weight.
7. The colored asphalt according to claim 6, characterized in that: The petroleum resin is one or more of coumarone resin, terpene resin and semi-hydrogenated petroleum resin.
8. The colored asphalt according to claim 6, characterized in that: The base oil is one or both of naphthenic oil and high aromatic oil.
9. The colored asphalt according to claim 6, characterized in that: The preparation method comprises the following steps: 1) After the base oil and SBS polymer are mixed, they are grown at a constant temperature of 130-140°C for 40-60 minutes, heated to 150-160°C, and nano zinc oxide is added at a stirring speed of 1000-2000 rpm, and stirring is continued for 30-50 minutes: 2) Add petroleum resin, continue stirring for 30-40 minutes after the petroleum resin is dissolved, and then place it in a constant temperature environment of 140-150℃ for 60-100 minutes.
Citation Information
Patent Citations
Asphaltum composite modified by particles / polymers, and preparation method
CN101050309A
SBS modified asphalt produced from MEREY-16 crude oil straight-run asphalt and preparation method thereof
CN106751966A
Namometer compound asphalt modifying agent and preparation method thereof
CN107227031A
Preparation method of exterior wall coating filled by modified nanometer zinc oxide
CN110591496A
Preparation method of high-activity nano zinc oxide
CN113353969A